Continuing cancer surgery through the first six months of the COVID‐19 pandemic at an academic university hospital in India: A lower‐middle‐income country experience. Issue 5 (10th February 2021) - Akhtar, Naseem; Rajan, Shiv; Chakrabarti, Deep; Kumar, Vijay; Gupta, Sameer; Misra, Sanjeev; Chaturvedi, Arun; Azhar, Tashbihul; Parveen, Shirin; Qayoom, Sumaira; Niranjan, Palavalasa; Tiwari, Shashwat
Abstract: Background: The novel coronavirus pandemic (COVID‐19) hinders the treatment of non‐COVID illnesses like cancer, which may be pronounced in lower‐middle‐income countries. Methods: This retrospective cohort study audited the performance of a tertiary care surgical oncology department at an academic hospital in India during the first six months of the pandemic. Difficulties faced by patients, COVID‐19‐related incidents (preventable cases of hospital transmission), and modifications in practice were recorded. Results: From April to September 2020, outpatient consultations, inpatient admissions, and chemotherapy unit functioning reduced by 62%, 58%, and 56%, respectively, compared to the same period the previous year. Major surgeries dropped by 31% with a decrease across all sites, but an increase in head and neck cancers ( p = .012, absolute difference 8%, 95% confidence interval [CI]: 1.75% — 14.12%). Postoperative complications were similar ( p = .593, 95% CI: −2.61% — 4.87%). Inability to keep a surgical appointment was primarily due to apprehension of infection (52%) or arranging finances (49%). Two COVID‐19‐related incidents resulted in infecting 27 persons. Fifteen instances of possible COVID‐19‐related mishaps were averted. Conclusions: We observed a decrease in the operations of the department without any adverse impact in postoperative outcomes. While challenging, treating cancer adequately during COVID‐19 can be accomplished by adequate screening and testing, and religiously following the prevention guidelines.